Studi Deskriptif Strategi Peningkatan Mutu Pendidikan Berbasis TQM (Total Quality Management) Era Pandemi TA 2020/2021 Di STT Kristus Alfa Omega - Tantri; Yoel Yulia; Franspebri (Sekolah Tinggi Teologi Nusantara, 2021)
Abstract:A quality improvement strategy based on TQM (Total Quality Management) is a quality improvement strategy that has emphasis on aspects including: customer satisfaction, continuous improvement, high obsession with quality, scientific approach to decision making, problem solving, and teamwork. and leadership. STT Kristus Alfa Omega Semarang is the locus of research where the respondents both leaders and students as respondents in this study. The purpose of the study was to find out how big the strategy for improving the quality of education based on TQM (total quality management) in the pandemic era at STT Kritsus Alfa Omega Semarang academic year 2020/2021. In this study, researchers used quantitative methods with descriptive research. This study is a one-variable study, with a total of 180 respondents and a sample of 119 students was taken. Data collection will be done using a questionnaire or questionnaire. The hypothesis test reads, it is suspected that the Strategy to Improve the Quality of Education Based on TQM (Total Quality Management) in the 2020/2021 Pandemic Era At STT Kristus Alfa Omega Semarang in the medium category or equal to 60% of the maximum value is not accepted. Based on the results of testing the quantitative data that have been described, it can be concluded that the value of the TQM-Based Education Quality Improvement Strategy is very high or 89% of the maximum value.